THE CONCEPT OF “HOME” IN THE LINGUISTIC PICTURE OF THE WORLD: A COMPARATIVE STUDY (Ustozlar uchun, 2025)
Abstract The article explores the concept of “home” as a key linguistic and cultural category reflecting human values, emotions, and worldview. The study aims to identify how the idea of “home” is verbalized and conceptualized in different linguistic pictures of the world, focusing on English and Russian. Through the analysis of lexical, phraseological, and metaphorical expressions, the research reveals both universal and culture-specific features of the “home” concept. It demonstrates that while “home” universally symbolizes safety, belonging, and emotional warmth, the cultural connotations differ: in English, “home” emphasizes individuality and comfort, whereas in Russian it reflects family ties and collective belonging. The comparative approach contributes to a deeper understanding of the interrelation between language, culture, and national mentality, confirming that the concept of “home” serves as a linguistic mirror of cultural identity and value orientation.